MAPbI3-quercetin perovskite material and preparation method and application thereof

By introducing quercetin into MAPbI3 material to modify its surface, the problem of instability of perovskite solar cell materials under external environmental stimulation is solved, its stability and photoelectric conversion efficiency are significantly improved, and its commercial application is promoted.

CN119463871APending Publication Date: 2025-02-18DALIAN NATIONALITIES UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411605585.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Perovskite solar cell materials are unstable under external environment stimulation and are prone to hydrolysis, oxidation and photodegradation, affecting their photoelectric properties and stability and hindering their commercial application.

Method used

By introducing quercetin into the MAPbI3 material, the surface of the material is modified by its hydrophobic groups and functional groups, improving its stability to water, oxygen and high temperatures, forming a stable MAPbI3-quercetin precursor, and through spin coating and annealing The treatment forms a perovskite film.

Benefits of technology

It significantly improves the water, oxygen and high temperature stability of MAPbI3 materials, extends its service life, enhances the photoelectric conversion efficiency and stability of perovskite solar cells, and provides a feasible solution for commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463871A_ABST
    Figure CN119463871A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of perovskite materials, and provides a preparation method of an MAPbI3-quercetin perovskite material, which comprises the following steps of: preparing an MAPbI3-quercetin precursor: adding lead iodide and methyl ammonium iodide into a reaction container, adding quercetin powder, adding polar solvents DMSO and DMF as solvents, fully mixing, and performing vacuum drying to obtain the MAPbI3-quercetin precursor; standing until the solution is completely clarified, so as to obtain an MAPbI3-quercetin precursor; and synthesizing the MAPbI3-quercetin perovskite material: carrying out cleaning treatment on FTO conductive glass, then carrying out ozone treatment, in a glove box, spin-coating the surface of the FTO conductive glass with an MAPbI3-quercetin precursor, then carrying out annealing treatment, and growing an MAPbI3-quercetin perovskite thin film on the surface of the FTO conductive glass, namely the MAPbI3-quercetin perovskite material. The invention also provides the MAPbI3-quercetin perovskite material and an application of the MAPbI3-quercetin perovskite material. The MAPbI3-quercetin perovskite material prepared by the preparation method disclosed by the invention provides a brand new solution for preparing an efficient and stable perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite materials, and in particular relates to a MAPbI3-quercetin perovskite material and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous consumption of non-renewable resources and the pollution of the environment by kerosene fuels, clean and renewable energy such as solar power generation and wind power generation have become the focus of research. However, although the conversion efficiency of commercial solar cells is constantly improving, there is still a certain gap with the theoretical limit. For example, traditional silicon-based solar cells, although the technology is relatively mature, their actual photoelectric conversion efficiency is usually around 20%-25%, which means that most of the solar energy is not fully utilized and converted into electrical energy.

[0003] Organic-inorganic perovskite solar cells (perovskite solar cells) have attracted widespread attention due to their high power conversion efficiency and simple solution processing capabilities. At present, the highest photoelectric conversion efficiency of all-perovskite tandem solar cells has reached 30.1%, showing great potential in the future photovoltaic field. However, due to its ionic properties (i.e., weak bonds between organic cations and inorganic components), perovskites are relatively unstable under the stimulation of the external environment. In a humid environment, perovskites will absorb moisture and undergo hydrolysis reactions, resulting in material structure destruction and performance degradation; when exposed to oxygen, perovskite materials are easily oxidized, affecting their photoelectric properties; long-term illumination will also cause perovskite materials to undergo photodegradation, reducing the efficiency and stability of the battery; this inherent instability poses challenges to the long-term application of perovskite solar cells, which may hinder their commercialization. Therefore, exploring and developing stable perovskite solar cells has very important scientific significance and social value. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a method for preparing a MAPbI3-quercetin perovskite material, aiming to solve the problems raised in the above-mentioned background technology.

[0005] The embodiment of the present invention is implemented as follows: a method for preparing a MAPbI3-quercetin perovskite material comprises the following steps:

[0006] (1) Preparing a MAPbI3-quercetin precursor: adding lead iodide and methylammonium iodide into a reaction vessel, adding quercetin powder at the same time, and then adding polar solvents DMSO and DMF as solvents to mix thoroughly, and standing until the solution is completely clear to obtain a MAPbI3-quercetin precursor;

[0007] (2) Synthesis of MAPbI3-quercetin perovskite material: The FTO conductive glass is cleaned and then treated with ozone. In a glove box, a MAPbI3-quercetin precursor is spin-coated on the surface of the FTO conductive glass, and then annealed. A MAPbI3-quercetin perovskite film is grown on the surface of the FTO conductive glass, namely, the MAPbI3-quercetin perovskite material.

[0008] Preferably, in step (1), the molar ratio of lead iodide to quercetin is 1:0.1 or 1:0.3.

[0009] Preferably, in step (1), the molar ratio of lead iodide to quercetin is 1:0.1.

[0010] Preferably, in step (2), the cleaning process is specifically as follows: the FTO conductive glass is cleaned with detergent and water to remove dust and debris on the surface, then subjected to ultrasonic vibration, and then cleaned with methanol to remove the surface aqueous solvent and residues, and then cleaned with acetone after ultrasonic vibration to remove oily stains, and then recovered acetone after ultrasonic vibration, and deionized water is added to cover the top of the FTO conductive glass to remove the residual cleaning solvent on the surface, and then the deionized water is poured out after ultrasonic vibration to dry the moisture on the surface of the FTO conductive glass.

[0011] Preferably, in step (2), the process of spin coating the MAPbI3-quercetin precursor on the surface of the FTO conductive glass is specifically as follows: placing the FTO conductive glass on a coating machine, placing the MAPbI3-quercetin precursor on the FTO and rotating it at a low speed of 600 rpm for 12 seconds, rotating it at a high speed of 2500 rpm for 30 seconds, and spinning chlorobenzene on the surface at the 21st second.

[0012] Preferably, in step (2), the annealing process is specifically as follows: after the coating is completed, annealing is performed at 60° C. for 5 minutes, and then annealing is performed at 100° C. for 10 minutes.

[0013] Another object of an embodiment of the present invention is to provide a MAPbI3-quercetin perovskite material, which is prepared by the above-mentioned preparation method.

[0014] Another object of an embodiment of the present invention is to provide an application of a MAPbI3-quercetin perovskite material in the preparation of a perovskite solar cell device.

[0015] Preferably, the MAPbI3-quercetin perovskite material is spin-coated on the FTO upper layer, and a silver electrode is plated on the surface to form a conductive loop.

[0016] The present invention provides a method for preparing a MAPbI3-quercetin perovskite material. The preparation method is simple, time-saving and low-cost. Quercetin having a hydrophobic group is introduced, and the water, oxygen and high temperature stability of MAPbI3 are improved through the surface modification of the hydrophobic group: hydroxyl (-OH) and keto group (C=O). Quercetin is added to the precursor and fully dissolved so that the hydrophobic group is added to the surface of MAPbI3, thereby obtaining a stable MAPbI 3- The quercetin precursor can obtain a more efficient perovskite solar cell by introducing functional groups to modify the surface defects. The MAPbI3-quercetin perovskite material prepared in the embodiment of the present invention provides a new solution for preparing efficient and stable perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A structural diagram of a perovskite solar cell device provided in Example 3 of the present invention;

[0018] Figure 2 SEM images of the perovskite films provided in Example 1 and Comparative Example 1 of the present invention (the upper one is Comparative Example 1, the lower one is Example 1);

[0019] Figure 3 The stability results of the perovskite solar cell devices provided in Example 3 and Comparative Example 2 of the present invention under 365nm ultraviolet light irradiation (the upper one is Example 3, and the lower one is Comparative Example 2);

[0020] Figure 4 The stability results of the perovskite solar cell devices provided in Example 3 and Comparative Example 2 of the present invention under water droplet erosion (the upper one is Example 3, and the lower one is Comparative Example 2);

[0021] Figure 5 The photocurrent response test results of the perovskite solar cell device provided in Example 3 of the present invention under irradiation with light of 530nm wavelength with a power of 91.74μW;

[0022] Figure 6 The morphology analysis results of the perovskite solar cell device provided in Example 3 of the present invention placed under 20% humidity for 30 days (the left one is before 30 days, and the right one is after 30 days). DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0024] A MAPbI3-quercetin perovskite material, the preparation method of which comprises the following steps:

[0025] (1) 1 mmol of PbI2 (lead iodide) and 1 mmol of MAI (methylammonium iodide) were placed in a vial, and quercetin powder was added to the reaction solution. Polar solvents DMSO (300 μL) and DMF (700 μL) were used as solvents to fully mix. After standing for 2 hours, the solution was completely clear to obtain MAPbI3-quercetin precursor.

[0026] (2) Place commercial etched FTO conductive glass (length and width 2cm*2cm, etching width 5mm, depth 500nm) in a beaker for cleaning. First, add detergent + water to the beaker to remove dust and debris on the surface, and cover the surface with plastic wrap to prevent dust from falling into the beaker and contaminating it again. After ultrasonically vibrating the beaker for 30 minutes, replace the cleaning solvent with methanol. Methanol is used to remove aqueous solvents and residues on the surface of FTO. After vibrating for 30 minutes, replace methanol with acetone to remove oily stains. After vibrating for 30 minutes, recover the acetone. Next, add deionized water to cover the top of FTO to remove residual methanol, acetone and other cleaning solvents on the surface. After vibrating for 30 minutes, pour out the deionized water, pierce the plastic wrap with air holes, and place it in a 70°C oven for 5 hours to dry the surface moisture for use.

[0027] Before spin coating, the cleaned FTO conductive glass was placed in the instrument for ozone treatment for 30 minutes to add hydrophilic groups to the surface and increase the adhesion of the solution. The treated FTO and MAPbI3-quercetin precursor were placed in a glove box to ensure that they were always in an inert gas environment during the synthesis process. The cleaned FTO was placed on a gelling machine, and 100 μL of MAPbI3-quercetin precursor was placed on the FTO and rotated at a low speed of 600 rpm for 12 seconds and at a high speed of 2500 rpm for 30 seconds. At the 21st second, 400 μL of chlorobenzene was spun on the surface. After the gelling was completed, annealing was performed at 60°C for five minutes and then at 100°C for ten minutes. A MAPbI3-quercetin perovskite film with a thickness of 50 μm was grown on the FTO surface.

[0028] The above-mentioned MAPbI3-quercetin perovskite film is used to prepare a stable transmission perovskite solar cell device, and its structure is as follows Figure 1 As shown, a MAPbI3-quercetin perovskite film is spin-coated on the FTO layer, and a 100 nm thick silver electrode is plated on the surface to form a conductive circuit.

[0029] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0030] Example 1: A MAPbI3-quercetin perovskite material, the preparation method of which comprises the following steps:

[0031] (1) 1 mmol of PbI2 (lead iodide) and 1 mmol of MAI (methylammonium iodide) were placed in a vial, and quercetin powder was added to the reaction solution at a molar ratio of PbI2 to quercetin of 1:0.1. Polar solvents DMSO (300 μL) and DMF (700 μL) were used as solvents to mix thoroughly. After standing for 2 hours, the solution was completely clear to obtain MAPbI3-quercetin precursor;

[0032] (2) Place commercial etched FTO conductive glass (length and width 2cm*2cm, etching width 5mm, depth 500nm) in a beaker for cleaning. First, add detergent + water to the beaker to remove dust and debris on the surface, and cover the surface with plastic wrap to prevent dust from falling into the beaker and contaminating it again. After ultrasonically vibrating the beaker for 30 minutes, replace the cleaning solvent with methanol. Methanol is used to remove aqueous solvents and residues on the surface of FTO. After vibrating for 30 minutes, replace methanol with acetone to remove oily stains. After vibrating for 30 minutes, recover the acetone. Next, add deionized water to cover the top of FTO to remove residual methanol, acetone and other cleaning solvents on the surface. After vibrating for 30 minutes, pour out the deionized water, pierce the plastic wrap with air holes, and place it in a 70°C oven for 5 hours to dry the surface moisture for use.

[0033] Before spin coating, the cleaned FTO conductive glass was placed in the instrument for ozone treatment for 30 minutes to add hydrophilic groups to the surface and increase the adhesion of the solution. The treated FTO and MAPbI3-quercetin precursor were placed in a glove box to ensure that they were in an inert gas environment during the synthesis process. The cleaned FTO was placed on a coater, and 100 μL of MAPbI3-quercetin precursor was placed on the FTO and rotated at a low speed of 600 rpm for 12 seconds and at a high speed of 2500 rpm for 30 seconds. At the 21st second, 400 μL of chlorobenzene was spun on the surface. After the coater was completed, annealing was performed at 60°C for five minutes and then at 100°C for ten minutes. A MAPbI3-quercetin perovskite film with a thickness of 50 μm was grown on the FTO surface.

[0034] Example 2: A MAPbI3-quercetin perovskite material, the preparation method of which comprises the following steps:

[0035] (1) 1 mmol of PbI2 (lead iodide) and 1 mmol of MAI (methylammonium iodide) were placed in a vial, and quercetin powder was added to the reaction solution at a molar ratio of PbI2 to quercetin of 1:0.3. Polar solvents DMSO (300 μL) and DMF (700 μL) were used as solvents for thorough mixing. After standing for 2 hours, the solution was completely clear to obtain MAPbI3-quercetin precursor.

[0036] (2) Place commercial etched FTO conductive glass (length and width 2cm*2cm, etching width 5mm, depth 500nm) in a beaker for cleaning. First, add detergent + water to the beaker to remove dust and debris on the surface, and cover the surface with plastic wrap to prevent dust from falling into the beaker and contaminating it again. After ultrasonically vibrating the beaker for 30 minutes, replace the cleaning solvent with methanol. Methanol is used to remove aqueous solvents and residues on the surface of FTO. After vibrating for 30 minutes, replace methanol with acetone to remove oily stains. After vibrating for 30 minutes, recover the acetone. Next, add deionized water to cover the top of FTO to remove residual methanol, acetone and other cleaning solvents on the surface. After vibrating for 30 minutes, pour out the deionized water, pierce the plastic wrap with air holes, and place it in a 70°C oven for 5 hours to dry the surface moisture for use.

[0037] Before spin coating, the cleaned FTO conductive glass was placed in the instrument for ozone treatment for 30 minutes to add hydrophilic groups to the surface and increase the adhesion of the solution. The treated FTO and MAPbI3-quercetin precursor were placed in a glove box to ensure that they were in an inert gas environment during the synthesis process. The cleaned FTO was placed on a coater, and 100 μL of MAPbI3-quercetin precursor was placed on the FTO and rotated at a low speed of 600 rpm for 12 seconds and at a high speed of 2500 rpm for 30 seconds. At the 21st second, 400 μL of chlorobenzene was spun on the surface. After the coater was completed, annealing was performed at 60°C for five minutes and then at 100°C for ten minutes. A MAPbI3-quercetin perovskite film will grow on the FTO surface.

[0038] Example 3: A perovskite solar cell device, the preparation method of which is as follows: spin coating the MAPbI3-quercetin perovskite film prepared in Example 1 on the upper layer of FTO, and coating a silver electrode with a thickness of 100 nm on the surface to form a conductive circuit.

[0039] Comparative Example 1: A MAPbI3 perovskite material, the preparation method of which comprises the following steps:

[0040] (1) 1 mmol of PbI2 (lead iodide) and 1 mmol of MAI (methylammonium iodide) were placed in a vial, and polar solvents DMSO (300 μL) and DMF (700 μL) were used as solvents to mix them thoroughly. After standing for 2 h, the solution was completely clear to obtain a MAPbI3 precursor.

[0041] (2) Place commercial etched FTO conductive glass (length and width 2cm*2cm, etching width 5mm, depth 500nm) in a beaker for cleaning. First, add detergent + water to the beaker to remove dust and debris on the surface, and cover the surface with plastic wrap to prevent dust from falling into the beaker and contaminating it again. After ultrasonically vibrating the beaker for 30 minutes, replace the cleaning solvent with methanol. Methanol is used to remove aqueous solvents and residues on the surface of FTO. After vibrating for 30 minutes, replace methanol with acetone to remove oily stains. After vibrating for 30 minutes, recover the acetone. Next, add deionized water to cover the top of FTO to remove residual methanol, acetone and other cleaning solvents on the surface. After vibrating for 30 minutes, pour out the deionized water, pierce the plastic wrap with air holes, and place it in a 70°C oven for 5 hours to dry the surface moisture for use.

[0042] Before spin coating, the cleaned FTO conductive glass is placed in the instrument for ozone treatment for 30 minutes to add hydrophilic groups to the surface and increase the adhesion of the solution. The treated FTO and MAPbI3 precursor are placed in a glove box to ensure that they are in an inert gas environment during the synthesis process. The cleaned FTO is placed on a coater, and 100 μL of MAPbI3 precursor is placed on the FTO and rotated at a low speed of 600 rpm for 12 seconds and at a high speed of 2500 rpm for 30 seconds. At the 21st second, 400 μL of chlorobenzene is spun on the surface. After the coater is completed, anneal at 60°C for five minutes and then at 100°C for ten minutes. A MAPbI3 perovskite film will grow on the FTO surface.

[0043] Comparative Example 2: A perovskite solar cell device, the preparation method of which is as follows: spin coating the MAPbI3 perovskite film prepared in Comparative Example 1 on the upper layer of FTO, and coating a silver electrode with a thickness of 100 nm on the surface to form a conductive circuit.

[0044] Comparative Example 3: A MAPbI3-quercetin precursor, the preparation method of which comprises the following steps:

[0045] 1 mmol of PbI2 (lead iodide) and 1 mmol of MAI (methylammonium iodide) were placed in a vial, and quercetin powder was added to the reaction solution at a molar ratio of PbI2 to quercetin of 1:0.05. Polar solvents DMSO (300 μL) and DMF (700 μL) were used as solvents and mixed thoroughly. After standing for 2 hours, the solution was completely clarified to obtain MAPbI3-quercetin precursor.

[0046] Comparative Example 4: A MAPbI3-quercetin precursor, the preparation method of which comprises the following steps:

[0047] 1 mmol of PbI2 (lead iodide) and 1 mmol of MAI (methylammonium iodide) were placed in a vial, and quercetin powder was added to the reaction solution at a molar ratio of PbI2 to quercetin of 1:0.2. Polar solvents DMSO (300 μL) and DMF (700 μL) were used as solvents and mixed thoroughly. After standing for 2 hours, the solution was completely clarified to obtain MAPbI3-quercetin precursor.

[0048] Performance Test:

[0049] In the process of preparing the precursor in Example 1, Example 2, Comparative Example 1, Comparative Example 3, and Comparative Example 4, quercetin powder was added to the reaction solution, and its excitation emission spectrum was measured to find that when the molar ratio of PbI2 to quercetin was 1:0.05, 1:0.1, 1:0.2, and 1:0.3, under 530nm wavelength light excitation, the luminescence intensity was 280.4%, 363.0%, 152.5% and 329.7% of the intrinsic MAPbI3, respectively. It can be seen that the molar ratio of PbI2 to quercetin in Example 1 and Example 2 can obtain better perovskite luminescence performance;

[0050] The perovskite films prepared in Example 1 and Comparative Example 1 were tested by scanning electron microscopy (SEM), and microscopic images were obtained as follows: Figure 2 As shown, according to Figure 2 It can be seen that at the scale of 400nm, there is a clear difference. The white stick-shaped protrusions are defective PbI2 on the surface of MAPbI3. In contrast, the structure of MAPbI3-quercetin is compact, making it difficult for the water and oxygen on the surface to promote the decomposition of MAPbI3 to form PbI2.

[0051] The stability test of the perovskite solar cell devices prepared in Example 3 and Comparative Example 2 was carried out, specifically:

[0052] The perovskite solar cell devices were placed under a 365nm commercial ultraviolet flashlight. Under the damage of continuous high-energy ultraviolet light, the results were as follows: Figure 3 As shown, according to Figure 3 It can be seen that after 450 mins, MAPbI3 was completely decomposed into yellow PbI2, while MAPbI3 with quercetin added did not produce visible decomposition;

[0053] 10 μL of deionized water was added to the surface of the perovskite solar cell device, and the results were as follows Figure 4 As shown, according to Figure 4It can be seen that the initial water droplet area is a circle with a diameter of 4 mm. After 3 hours of diffusion, the perovskite material on the MAPbI3 surface is completely destroyed and a large PbI2 area and film are formed in the middle. However, for MAPbI3-quercetin, only a circular PbI2 decomposition area with a diameter of 4 mm exists until the water is completely diffused. This is because the organic ligands added to the surface hinder the penetration and movement of water molecules on the surface.

[0054] The perovskite solar cell device prepared in Example 3 was subjected to a photocurrent response test under irradiation with a wavelength of 530 nm and a power of 91.74 μW. Figure 5 As shown, according to Figure 5 It can be seen that when no external bias is applied, the maximum photocurrent reaches the milliampere level, and the device light detection rate is ≥10 8 Jones, the response / recovery time is in the μs range;

[0055] The perovskite solar cell device prepared in Example 3 was placed under 20% humidity for 30 days for morphological analysis. The comparison results are as follows: Figure 6 As shown, according to Figure 6 It can be seen that after 30 days of storage, there is no visible precipitation of PbI2 and the photoelectric conversion efficiency remains at 90% of the initial level.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MAPbI3-quercetin perovskite material, characterized in that: The following steps are involved: (1) Preparing a MAPbI3-quercetin precursor: adding lead iodide and methylammonium iodide into a reaction vessel, adding quercetin powder at the same time, and then adding polar solvents DMSO and DMF as solvents to mix thoroughly, and standing until the solution is completely clear to obtain a MAPbI3-quercetin precursor; (2) Synthesis of MAPbI3-quercetin perovskite material: The FTO conductive glass is cleaned and then treated with ozone. In a glove box, a MAPbI3-quercetin precursor is spin-coated on the surface of the FTO conductive glass, and then annealed. A MAPbI3-quercetin perovskite film is grown on the surface of the FTO conductive glass, namely, the MAPbI3-quercetin perovskite material.

2. The method for preparing the MAPbI3-quercetin perovskite material according to claim 1, characterized in that: In step (1), the molar ratio of lead iodide to quercetin is 1:0.1 or 1:0.

3.

3. The method for preparing the MAPbI3-quercetin perovskite material according to claim 2, characterized in that: In step (1), the molar ratio of lead iodide to quercetin is 1:0.

1.

4. The method for preparing the MAPbI3-quercetin perovskite material according to claim 1, characterized in that: In step (2), the cleaning process is specifically as follows: the FTO conductive glass is cleaned with detergent and water to remove dust and debris on the surface, then subjected to ultrasonic vibration, and then cleaned with methanol to remove the surface aqueous solvent and residues, and then cleaned with acetone after ultrasonic vibration to remove oily stains, and then recovered acetone after ultrasonic vibration, and deionized water is added to cover the top of the FTO conductive glass to remove the residual cleaning solvent on the surface, and then the deionized water is poured out after ultrasonic vibration to dry the moisture on the surface of the FTO conductive glass.

5. The method for preparing the MAPbI3-quercetin perovskite material according to claim 1, characterized in that: In step (2), the process of spin coating the MAPbI3-quercetin precursor on the surface of the FTO conductive glass is specifically as follows: placing the FTO conductive glass on a coating machine, placing the MAPbI3-quercetin precursor on the FTO and rotating it at a low speed of 600 rpm for 12 seconds, rotating it at a high speed of 2500 rpm for 30 seconds, and spinning chlorobenzene on the surface at the 21st second.

6. The method for preparing the MAPbI3-quercetin perovskite material according to claim 1, characterized in that: In step (2), the annealing process is specifically as follows: after the coating is completed, annealing is performed at 60° C. for 5 minutes, and then annealing is performed at 100° C. for 10 minutes.

7. A MAPbI3-quercetin perovskite material, characterized in that: The material is prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the MAPbI3-quercetin perovskite material as claimed in claim 7 in the preparation of a perovskite solar cell device.

9. The use according to claim 8, characterized in that: The MAPbI3-quercetin perovskite material is spin-coated on the FTO layer, and a silver electrode is plated on the surface to form a conductive loop.